Mechanisms Underlying the Antidepressant Effect of Acupuncture via the CaMK Signaling Pathway - Bai, Lu; Zhang, Di; Cui, Tao-Tao; Li, Ji-Fei; Gao, Yang-Yang; Wang, Nan-Yi; Jia, Peng-Li; Zhang, Hui-yuan; Sun, Zhong-Ren; Zou, Wei; Wang, Long (Frontiers in Behavioral Neuroscience, 2020)
The CaMK pathway has been proven to play an important role in regulating cognitive function and emotional response. Acupuncture through the CaMK pathway improves depression-like behavior and the molecular mechanism related to its antidepressant remains to be explored. In this study, we aimed to determine whether the ability of acupuncture at Baihui (GV20) and Shenting (GV24) points to treat depression is related to the regulation of key proteins in the CaMK pathway. A rat model of depression was induced by chronic unpredicted mild stress (CUMS). Model rats in the electroacupuncture group were subjected to acupuncture at the Baihui (GV20) and Shenting (GV24) acupoints once a day for 20 min. Model rats in the fluoxetine group were gavaged with fluoxetine (1.8mg/kg). Immunohistochemistry and Western blotting assays were used to evaluate immunoreactivity for and the protein expression levels of CaMKII, CaMKIV, and CaM. The results showed that electroacupuncture had a significant effect in rats with depression. Electroacupuncture and fluoxetine regulated the expression of key proteins in the CaMK signaling pathway, which is related to depression, in the hippocampi of rats. This indicates that acupuncture at Baihui (GV20) and Shenting (GV24) may alleviate depressive symptoms and reduce work- and life-related burdens and stress by regulating the CaMK signaling pathway.